Audience leisure involvement, satisfaction and behavior intention at the Macau Science Center. Issue 2 (2nd March 2020) - Li, Zhi; Ge, Yuemeng; Su, Zegang; Huang, Xiaohua
Abstract : Purpose: This study aims to analyze the basic information of visitors of the Macau Science Center to assess their leisure involvement, satisfaction and behavioral intention, along with the interaction of these factors. Suggestions are made for museum policy modifications to improve visitor experience quality. Design/methodology/approach: The analysis methods used in this study included reliability, descriptive statistics, independent-samples t test, ANOVA, correlation analysis and regression analysis. Findings: The results showed that there was no significant relationship between gender and satisfaction, involvement of leisure or behavioral intention; age and educational level had significant impacts on satisfaction, leisure involvement and behavioral intention; significant differences were found in terms of visitors' point of geographic origin, namely, local residents, mainland residents and Hong Kong residents; occupation was found to have no significant impact on satisfaction, leisure involvement or behavioral intention; monthly income was found to have no significant impact on leisure involvement and behavioral intention, but did have a significant impact on satisfaction; number of visits had no significant impact; there was no significant difference in leisure involvement and behavioral intention among different types of visitors, but there was a significant difference in terms of satisfaction; and significant correlations were found between leisure involvement and behavioral intentions. Originality/value: The value of this study is to identify problems and offer potential solutions for the improvement of the Macau Science Center by studying the leisure involvement, satisfaction and behavioral intention of museum visitors. The proposed measures can improve the visibility and quality of the science museum, attract additional visitors and improve Macau's branding through promoting science education and tourism.